The Impact of Inheritance on the Distribution of Wealth: Evidence from China. (16th April 2021) - Wei, Hongyao; Yang, Zhengyi
Abstract : Using the China Health and Retirement Longitudinal Study, we investigate household inheritances' structural characteristics and their effects on wealth distribution. First, we find that the proportion of households receiving inheritances in China is slightly lower than that of some European countries and the United States, and the inheritance scale, especially the proportion of inheritances in household net worth, is much lower. Second, inheritances can significantly promote wealth accumulation, and wealthy households are more likely to receive larger‐scale inheritances. Therefore, inheritances can aggravate class stratification and reduce social mobility. Third, inheritances reduce relative wealth inequality but widen the absolute wealth gap. This effect's duality is that although wealthy households have inheritances on a larger scale, the relative importance of the inheritance is more significant for poorer households, who inherit more relative to their household net worth. Altruistic motivations of inheritance donors can help explain this phenomenon.